THE ROLE OF FEMALE SEX HORMONES AND LACTOBACILLI ON GENITAL EPITHELIAL CELL BARRIER FUNCTIONS AND INNATE IMMUNE RESPONSES IN THE PRESENCE AND ABSENCE OF HIV - Dizzell, Sara (My University, 2017)
Background: Approximately 40% of global human immunodeficiency virus-1 (HIV) transmission occurs in the female genital tract (FGT). Epithelial cells lining the FGT comprise the first barrier to HIV-1 entry. The functions of these cells are influenced by female sex hormones and the mucosal microbiota. Studies have suggested that hormonal environment and a dysbiosis of the FGT microbiota may lead to inflammation in the genital mucosa and enhance HIV acquisition. A Lactobacillus dominant microenvironment in the FGT is considered to have protective functions against sexually transmitted pathogens, however the interaction between sex hormones and lactobacilli and their effect on epithelial cell functions remains to be determined. Methods of Study: For these studies, primary genital epithelial cells (GECs) were isolated from hysterectomy tissues obtained following patient consent. GEC cultures were grown to confluence on cell culture inserts in the presence or absence of the female sex hormones estrogen (E2), progesterone (P4), or medroxyprogesterone acetate (MPA). Polarized monolayers were exposed to two probiotic strains of Lactobacillus: L. reuteri (RC-14) or L. rhamnosus (GR-1), or the most common strain of bacteria found in the FGT, L. crispatus in the presence or absence of HIV-1. Cell viability, barrier integrity, and innate inflammatory factors were among the primary measures performed. Results: In our system, cell viability was unaltered in the presence of Lactobacillus species and/or female sex hormones. All three strains of bacteria (L. crispatus and probiotic lactobacilli GR-1 and RC-14) significantly increased GEC barrier integrity, as measured by transepithelial electrical resistance (TER). Both GR-1 and RC-14 significantly reduced GEC barrier permeability as measured by a dextran dye leakage assay, whereas L. crispatus did not. Conversely, hormones did not alter barrier integrity nor barrier permeability. However, hormones did alter secretion of cytokines and chemokins by GECs. GECs grown in the presence of estrogen decreased TNF-α, IL-1α, IL-1β and IL-8 secretion in comparison to no hormone treatment, while GECs grown in the presence of MPA significantly decreased MIP-1α and TNF-α secretion. In the presence of HIV both GR-1 and RC-14 were able to confer an increase in barrier integrity similar to that observed with GR-1 and RC-14 treatment alone. Addionally, GECs grown in the presence of E2 and MPA displayed a less inflammatory (TNF-α, IL-1α, and IL-1β) environment when exposed to HIV compared to no hormone and P4. Interstingly, the decrease in inflammation was not observed when measuring chemokines such as IL-8 and RANTES. Furthermore, probiotic bacteria were able to significantly reduce HIV mediated increases in TNF-α when grown in the presence of no hormone, P4, and MPA. A similar trend was observed for GECs grown in the presence of E2 however, given that E2 reduced the TNF-α response mediated by HIV, results were not significant. Overall, probiotic lactobacilii GR-1 and RC-14 enhanced GEC barrier functions while E2 and MPA appeared to exert an anti-inflammatory effect on epithelial cell innate responses in both the presence and absence of HIV. Conclusions: In our system, probiotic lactobacilli enhanced GEC barrier functions and estrogen appeared to exert an anti-inflammatory effect on epithelial innate responses. Enhanced barrier function and decreased inflammation correlate with decreased in HIV acquisition and replication. These studies provide an insight into how factors in the genital microenvironment can affect HIV acquisition in the FGT, and will subsequently assist in the development of prophylactic strategies to reduce HIV transmission.
Keywords: Epithelial Cells; Hormones; HIV; Microbiota; Lactobacilli